The patient's level of knowledge about analgesic drug self-medication - Yuniharce Kadang; Fatun Sulaturrahma (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Self-medication is the practice of using drugs without a doctor's prescription to overcome minor health problems, one of which is analgetic drugs to reduce pain. Although self-medication can improve the accessibility of medications, improper use can be risky for the patient's health. Adequate knowledge of the types, dosages, and ways of using analgesic medications is essential to ensure effectiveness and avoid adverse side effects. This study aims to evaluate the level of patient knowledge about analgetic drug self-medication. Methods: This study uses a quantitative design with a survey approach. Data was collected through a questionnaire distributed to 81 patients who visited the pharmacy. Results: The results of this study indicate that the percentage of respondents' answers is 8.091%. Based on these results, it can be concluded that the level of patient knowledge about self-medication of analgtic drugs is in a good category. Conclusions: The results showed that the majority of patients had sufficient knowledge about the indications and dosage of analgetic drugs, but there was a gap in understanding of potential side effects and drug interactions. This indicates the need for more intensive health education regarding self-medication, especially in the use of analgesic drugs, to reduce the risk of inappropriate use